Dendritic poly-chelator frameworks for multimeric bioconjugation. Issue 17 (13th February 2017) - Reich, Dominik; Wurzer, Alexander; Wirtz, Martina; Stiegler, Veronika; Spatz, Philipp; Pollmann, Julia; Wester, Hans-Jürgen; Notni, Johannes
Abstract : Dendrimers built of chelators show unparalleled Ga(III) complexation efficiency and allow for synthesis of highly symmetrical bifunctional poly-bioconjugates via Click-Chemistry. Abstract : Starting from multifunctional triazacyclononane-triphosphinate chelator cores, dendritic molecules with the ability to bind metal ions within their framework were synthesized. A cooperative interaction of the chelator cages resulted in a markedly increased affinity towards 67/68 Ga III . A hexameric PSMA inhibitor conjugate with high affinity (IC50 = 1.2 nM) and favorable in vivo PET imaging properties demonstrated practical applicability. The novel scaffolds are useful for synthesis of structurally well-defined multimodal imaging probes or theranostics.